Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Answer:
Suppose we have an equation like:
[tex]\frac{A}{C} = \frac{B}{D}[/tex]
If we want to remove the denominators, we should multiply both sides by each denominator.
First, let's multiply both sides by C.
[tex]\frac{A}{C}*C = \frac{B}{D}*C[/tex]
[tex]A = \frac{B}{D}*C[/tex]
Now let's multiply both sides by D.
[tex]A*D = \frac{B}{D}*C*D[/tex]
[tex]A*D = B*C[/tex]
So now we removed the denominators.
Now let's do this to our expression.
[tex]2 - \frac{3}{4*x} = \frac{9}{10}[/tex]
First, let's multiply both sides by 10
[tex](2 - \frac{3}{4*x})*10 = \frac{9}{10}*10[/tex]
[tex]20 + \frac{30}{4*x} = 9[/tex]
Now let's multiply both sides by 4*x
[tex](20 + \frac{30}{4*x})*4*x = 9*4*x[/tex]
[tex]20*4*x - 30 = 9*4*x[/tex]
[tex]80*x - 30 = 36*x[/tex]
Now we can solve this for x:
[tex]80*x - 36*x = 30[/tex]
[tex]44*x = 30[/tex]
[tex]x = \frac{30}{44} = 0.68[/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.